A modified version of the Molly rumen model to quantify methane emissions from sheep. Issue 7 (1st July 2015) - Vetharaniam, I.; Vibart, R. E.; Hanigan, M. D.; Janssen, P. H.; Tavendale, M. H.; Pacheco, D.
Abstract: We modified the rumen submodel of the Molly dairy cow model to simulate the rumen of a sheep and predict its methane emissions. We introduced a rumen hydrogen (H2 ) pool as a dynamic variable, which (together with the microbial pool in Molly) was used to predict methane production, to facilitate future consideration of thermodynamic control of methanogenesis. The new model corrected a misspecification of the equation of microbial H2 utilization in Molly95, which could potentially give rise to unrealistic predictions under conditions of low intake rates. The new model included a function to correct biases in the estimation of net H2 production based on the default stoichiometric relationships in Molly95, with this function specified in terms of level of intake. Model parameters for H2 and methane production were fitted to experimental data that included fresh temperate forages offered to sheep at a wide range of intake levels and then tested against independent data. The new model provided reasonable estimates relative to the calibration data set, but a different parameterization was needed to improve its predicted ability relative to the validation data set. Our results indicate that, although feedback inhibition on H2 production and methanogen activity increased with feeding level, other feedback effects that vary with diet composition need to be considered in future work on modeling rumen digestion in Molly.